Shrinkage of Concrete Panels Made with Recyclable Concrete Aggregates - Soomro, F. A.; Memon, B. A.; Oad, M.; Buller, A. H.; Tunio, Z. A. (Engineering, Technology & Applied Science Research, 2019)
An experimental study on the shrinkage of recyclable aggregate concrete panels is presented in this paper. Recyclable aggregates are used in 50%, 60%, 70% and 80% replacement of natural coarse aggregates. For each replacement percentage, 3 panels were cast using 1:2:4 mix with 0.54 water-cement ratio and were cured for 28 days. In addition, 3 panels with the same parameters but using all-natural coarse aggregates were also cast to compare the results. Shrinkage in all panels was recorded for 3 months. Comparison of results reveals that with a 50% replacement, 8.33% increase in shrinkage was recorded. Along with shrinkage, cracks were also observed. At the end of the three month period, the widest crack had less width than 1mm, showing good resistance of the proposed material to shrinkage. Concluding, 50% replacement can be used in new concrete.